PENGARUH TERPAAN BERITA NEGATIF MENGENAI INVESTASI DAN TERPAAN KONTEN SOSIAL MEDIA INSTAGRAM IPOT TERHADAP MINAT BERINVESTASI MENGGUNAKAN APLIKASI IPOT - Jan Khairuzzaman, Alief; Surayya Ulfa, Nurist; Suryanto Gono, Joyo Nur (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The background of this research is the problem of the many negative news about investments such as fraudulent investments, trading robot scams, investor data leaks, investment application errors, and other negative news. These negative news can be one of the factors that reduce public interest in investing using the application. One of the investment application providers, IPOT, offsets the negative news by uploading content through social media with the aim of increasing public interest in investing using applications, especially IPOT. This study aims to see the influence between exposure to negative news about investment and exposure to IPOT Instagram social media content on interest in investing using IPOT. This research is an explanatory quantitative research, the sampling technique used is non-probability sampling with purposive sampling method. Data collection was carried out using a questionnaire instrument distributed to 100 respondents. The results of this study indicate that exposure to negative news about investment and exposure to IPOT Instagram social media content are significant and have a simultaneous influence on interest in investing using IPOT. This is in line with Information Integration Theory. Thus, although negative news about investment is still circulating both now and in the future, it can be balanced with IPOT's Instagram social media content to increase people's interest in investing using IPOT.